Inequality in pupils' educational attainment: How much do family, sibling type and neighbourhood matter? - Cheti Nicoletti; Birgitta Rabe (University of Essex, Institute for Social and Economic Research (ISER), 2010)
We explore the relative influence of family and neighbourhood on educational attainment and how this varies by sibling type. Using English register data we find sibling correlations in exam scores of 0.563 at the end of primary school and of 0.621 at the end of compulsory schooling. The neighbourhood explains at most 10-15% of the variance in educational attainment; whereas the family explains at least 43%. This percentage is significantly higher for twins and for siblings of the same sex. It is also higher for closely spaced siblings and siblings with a similar school starting age but only at age 11.
Keywords: J13; R23; 330; siblings; twins; neighbourhood; educational attainment; multilevel model; Schüler; Bildungsertrag; Familie; Soziale Gruppe; Wohnstandort; Großbritannien